ZMOT BRAND STORIES AS STIMULUS AND EFFECT ON PROSPECTIVE STUDENTS OF HEIs IN THE COVID-19 PANDEMIC ERA - Amalia E. Maulana; Deva P. Setiawan, (Malaysian Journal of Business and Economics (MJBE), 2022)
The current pandemic significantly prompts rising information gathering activities via the internet associated with a brand story. This phenomenon has considerable impacts in the decision-making process of high involvement services such as higher education. Since prospective students no longer have the opportunity to directly visiting the campus, their effort inclines more towards reading about life activities and experiences’ stories from those who already encounter university life. This study utilizes a qualitative approach to gain deeper insights into this relatively prevailing Covid-19 pandemic situation by conducting a netnography and in-depth interviews with current and prospective students. This study discovers that diverse online learning experiences recounted by current students during the pandemic are brand story manifestations, shown as content in social media platforms. Furthermore, the finding emphasizes the importance of the upperclassmen role to the prospective students. They can associate with the prospective students while maintaining credibility as an influencer. Inspiring experiences told in university seniors positive narratives become successful zero moments of truth (ZMOT) and enhance the desire to interact with that remarkable university brand. Conversely, unpleasant encounters would be an adverse stimulus that would dissuade further interaction between prospective students and the particular university brand, revealed either through behavior or attitude. ZMOT brand story is uncontrollable content in social media, and if HE marketers neglect them, it will obstruct the development of the university's image. HE marketers need to be alert with diverse stories derived from personal experiences of online classes during the pandemic. Cooperation with the service provider, aka faculty members, has never been more profound to ensure that the delivery of the materials is enjoyable and memorable.